2002
DOI: 10.1128/mcb.22.8.2556-2563.2002
|View full text |Cite
|
Sign up to set email alerts
|

Central Role for the XRCC1 BRCT I Domain in Mammalian DNA Single-Strand Break Repair

Abstract: The DNA single-strand break repair (SSBR) protein XRCC1 is required for genetic stability and for embryonic viability. XRCC1 possesses two BRCA1 carboxyl-terminal (BRCT) protein interaction domains, denoted BRCT I and II. BRCT II is required for SSBR during G 1 but is dispensable for this process during S/G 2 and consequently for cell survival following DNA alkylation. Little is known about BRCT I, but this domain has attracted considerable interest because it is the site of a genetic polymorphism that epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
129
4
3

Year Published

2003
2003
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(148 citation statements)
references
References 54 publications
12
129
4
3
Order By: Relevance
“…These epidemiological results therefore do not provide any conclusive evidence of a direct association of the XRCC1 R399Q SNP with cancer. This conclusion is further supported by a functional study by Taylor et al (2002) using transfected CHO cells deficient in XRCC1 gene product. Cells with the R399Q genotype showed no difference in sensitivity to MMS than cells transfected with Q399R.…”
Section: R399qmentioning
confidence: 56%
See 2 more Smart Citations
“…These epidemiological results therefore do not provide any conclusive evidence of a direct association of the XRCC1 R399Q SNP with cancer. This conclusion is further supported by a functional study by Taylor et al (2002) using transfected CHO cells deficient in XRCC1 gene product. Cells with the R399Q genotype showed no difference in sensitivity to MMS than cells transfected with Q399R.…”
Section: R399qmentioning
confidence: 56%
“…It is also the site for direct binding to both gapped and nicked DNA, and gapped DNA complexed with POL b (Marintchev et al, 1999). XRCC1 has two BRCT domains, which are weakly conserved motifs first identified in BRCA1, and which mediate protein interactions (Zhang et al, 1998;Taylor et al, 2002;Beernink et al, 2005). BRCT1 is an interactive site for PARP whereas BRCT2 is an interactive binding site for Lig3.…”
Section: Xrcc1 Structurementioning
confidence: 99%
See 1 more Smart Citation
“…28 In contrast, an experimental study reported that the Arg399Gln polymorphism does not affect the DNA repair function, suggesting that it has little or no biological impact on cancer susceptibility. 29 Studies on the Arg194Trp polymorphism have produced inconsistent results with respect to the risk of various cancers, even though most published studies have reported a reduced risk of cancer for the 194Trp allele. 30 The inconsistent results of association studies between the polymorphisms and cancer risk may be due to linkage disequilibrium with a determinant variant of the XRCC1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large set of data implying the functional importance of the XRCC1-399 polymorphism with the variant Gln allele being associated with a decreased capacity to repair DNA damage and a consequent increased level of DNA damage (Lunn et al, 1999;Duell et al, 2000;Au et al, 2003;Wang et al, 2003;Vodicka et al, 2004). However, contradictory findings have also been reported including a study by (Taylor et al, 2002) who examined the polymorphism in an isogenic cellular background and demonstrated no effect upon the BRCT-mediated functions of XRCC1; instead, it was suggested that potentially functional polymorphisms in neighbouring DNA repair genes may be genetically linked.…”
Section: Base Excision Repairmentioning
confidence: 74%